2000
DOI: 10.1002/1097-4539(200009/10)29:5<343::aid-xrs414>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Capillary optics and their use in x-ray analysis

Abstract: The use of polycapillary lenses in x‐ray microanalysis and x‐ray diffractometry is considered. Lenses with focal spot diameters from 0.5–1 mm down to 5–10 µm ensure an increased flux on the sample under investigation by 2–3 orders of magnitude. The combination of a standard microfocus x‐ray tube of 50–100 W power with such a lens permits fluxes to be obtained comparable to those at workstations for microanalysis attached to a synchrotron. The use of polycapillary lenses requires specialized x‐ray tubes. A new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The appearance of X ray optics has allowed us to distinguish some directions in the development X ray fluorescence analysis of solu tions. Thus, the use of X ray semilenses [11] for the transformation of primary radiation into quasiparallel beams focused on the spot from the dried analyzed liq uid seems quite promising for the improvement of the above described procedure by the Rigaku Corporation [13]. Lenses with a wide capture angles, which ensure the focusing of the entire primary beam on the sample, would allow a change to low power sources (several watts) and simple recording devices utilizing the energy dispersive principle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The appearance of X ray optics has allowed us to distinguish some directions in the development X ray fluorescence analysis of solu tions. Thus, the use of X ray semilenses [11] for the transformation of primary radiation into quasiparallel beams focused on the spot from the dried analyzed liq uid seems quite promising for the improvement of the above described procedure by the Rigaku Corporation [13]. Lenses with a wide capture angles, which ensure the focusing of the entire primary beam on the sample, would allow a change to low power sources (several watts) and simple recording devices utilizing the energy dispersive principle.…”
Section: Resultsmentioning
confidence: 99%
“…Preliminary investigations have shown that the sophistication of the sorption-X ray fluorescence method, in particu lar, the reduction of the volumes of analyzed samples and even the change to the microanalysis of solutions, the further reduction of the limits of detection and the duration of analysis are associated with the possibility of focusing of the irradiating X ray beam [8,9]. A sim ilar problem for direct X ray fluorescence microanal ysis was solved using systems of polycapillary X ray optics (polycapillary lenses) proposed by one of authors of this paper [10][11][12].…”
mentioning
confidence: 99%
“…Recently, a confocal micro‐XRF analysis has been developed . In our laboratory, a high resolution confocal micro‐XRF instrument equipped with a vacuum chamber has been developed .…”
Section: Introductionmentioning
confidence: 99%
“…Later, equipping the detector with a second polycapillary lens, a new concept based on a confocal configuration was proposed. Indeed, the detected signal comes from the intersect between the volume excited nearby the source lens focal plane and the analyzed volume in the vicinity of the detector lens focal plane [11-15]. The spatial resolution of the confocal micro-XRF technique is thus enhanced compared to the classical configuration.…”
Section: Introductionmentioning
confidence: 99%